Question
Solve \( 5(4 m+1)-2 m=-13 \)
Ask by Salazar Cruz. in the United States
Feb 04,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
\( m = -1 \)
Solution
To solve the equation \( 5(4m + 1) - 2m = -13 \) for \( m \), follow these steps:
1. **Distribute the 5 into the parentheses:**
\[
5 \times 4m + 5 \times 1 - 2m = -13
\]
\[
20m + 5 - 2m = -13
\]
2. **Combine like terms (combine \( 20m \) and \( -2m \)):**
\[
(20m - 2m) + 5 = -13
\]
\[
18m + 5 = -13
\]
3. **Subtract 5 from both sides to isolate the term with \( m \):**
\[
18m + 5 - 5 = -13 - 5
\]
\[
18m = -18
\]
4. **Divide both sides by 18 to solve for \( m \):**
\[
m = \frac{-18}{18}
\]
\[
m = -1
\]
**Solution:** \( m = -1 \)
Reviewed and approved by the UpStudy tutoring team
Like
error msg
Explain
Simplify this solution
Mind Expander
To solve the equation \( 5(4m + 1) - 2m = -13 \), first, distribute the 5: \[ 20m + 5 - 2m = -13 \] Next, combine like terms: \[ (20m - 2m) + 5 = -13 \] \[ 18m + 5 = -13 \] Now, isolate the term with \( m \) by subtracting 5 from both sides: \[ 18m = -13 - 5 \] \[ 18m = -18 \] Finally, divide both sides by 18: \[ m = -1 \] So, the solution is \( m = -1 \).